DIKSI DAN BAHASA FIGURATIF SASTRA PERJALANAN DALAM ANTOLOGI PUISI A ROMANTIC JOURNEY THE BEGINNING KARYA DESI ANWAR: KAJIAN STILISTIKA - Enung Nurhayati; Yayu Wahyuni Hidayati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to describe the form, meaning, and function of diction and figurative literary language of the journey contained in a collection of poems by A Romantic Journey the Beginning by Desi Anwar. Desi Anwar's method of stylistic assessment of ARJTB used in this study is descriptive-analysis through literature studies. The technique used in this study is by collecting data in the form of documentation, namely from ARJTB poetry by Desi Anwar as the research material object. While the formal object is the diction and figurative literature of travel. The results showed: (1) Studying denotative and connotative diction, the choice of words in my lyrics shows that the contents of ARJTB poetry are not merely channeling factual information but there are convincing goals, persuading, reminding, and insinuating with contextual understanding of a particular culture; (2) The figurative language in ARJTB's poetry hides the true meaning with an image and the poet has tricks to create a richer, more effective, and more suggestive effect in the language of poetry; (3) By Meaning, the ARJTB poem contains a fairly detailed description of the author's experience and perception of a place. I lyrics can give pragmatic information about a place visited and a description of people's culture through the author's perception; (4) The function of travel literature can analogize a story of narration and change one's intellectual attitudes to be wiser and pay attention to the meaning of beauty in every corner of the place (spot) that has been explored